Assessment in counseling : practice and applications - Balkin, Richard S. (New York : Oxford University Press, 2018)
"We focus on the application of the theoretical and measurement concepts of assessment in counseling. We use a conversational style of writing and emphasize the skills used in assessment. In this book we present theoretical basis of assessment and emphasize the practical components to enhance practice in counseling"--
The role of assessment in counseling -- Case studies progress notes: classification systems -- Fundamentals of assessment -- Current standards for validity -- Current standards for reliability -- How to choose an assessment instrument -- Conducting an initial interview -- Multicultural and special population assessment issues -- In counseling -- Fundamentals of ability assessment -- Fundamentals of career assessment -- Marriage, substance abuse, and suicide assessment -- Fundamentals of interpretation assessment -- Assessment of accountability in counseling.
Includes bibliographical references (pages [257]-265) and index.
Keywords: Psychological tests; Counseling